THE BOR-HAD APPLICATION: A CONCEPTUAL INNOVATION IN ISLAMIC EDUCATION WITH UMI PRINCIPLES - Tuan Kechik, Tuan Siti Mastazameatun Long; Mansor@Noordin, Nur Azwani; Kamil, Mohd Faizul Aziz; Yusri, Nur Alya Fatihah (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2026)
The rapid expansion of digital integration across the global educational sector, which was profoundly catalysed by the recent COVID-19 health crisis, highlights a critical demand for pioneering and ethics-centred technological advancements, especially in Islamic academic environments. This study presents a conceptual exploration of Bor-Had, a proposed digital architecture for student attendance management. Beyond merely streamlining administrative accuracy and institutional communication, Bor-Had is engineered to embody the foundational governance pillars of Kelantan: ‘Ubudiyyah (devotion), Mas’uliyyah (accountability), and Itqan (excellence). By utilizing a conceptual framework analysis, this research evaluated how the intended functionalities of Bor-Had align with these UMI principles to validate its necessity as a value-based innovation. The investigation indicates that the system’s automated features and live data analytics are specifically crafted to support ‘Ubudiyyah by reclaiming time for essential educational and religious activities. Additionally, the system’s commitment to transparent and reliable data logs is expected to strengthen Mas’uliyyah. At the same time, Bor-Had’s focus on technical exactness, and the removal of operational flaws is positioned to advance Itqan. As a major development in the digitalization of Islamic learning, this conceptual model provides a standard for ‘Sharia-Compliant by Design technology. These innovations ensure that software architectures not only harmonize with but actively reinforce Islamic moral values. The study highlights Bor-Had’s capacity to build more robust and flexible Islamic academic systems, guaranteeing that technical upgrades are in direct service to spiritual goals. Finally, the paper outlines significant implications and prospective research paths for the moral and efficient adoption of value-integrated technology.